2020
DOI: 10.1123/ijspp.2019-0310
|View full text |Cite
|
Sign up to set email alerts
|

Pole Length’s Influence on Performance During Classic-Style Snow Skiing in Well-Trained Cross-Country Skiers

Abstract: Purpose: To investigate how self-selected pole length (PL) of ∼84% (PL84%) compared with ∼90% (PL90%) of body height influenced performance during a 700-m time trial with undulating terrain on snow. Methods: Twenty-one cross-country skiers, 7 of whom were women, performed 4 trials at a maximal effort in a counterbalanced fashion with PL84% and PL90% separated by 20-minute breaks between trials. In trials I and II, only double poling was allowed, while in trials III and IV, skiers used self-selected classical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…While the superior improvement in the initial 200 m may be explained by faster acceleration, as previously shown for double poling in the studies by Hansen, Losnegard [8] and Losnegard et al [14], better section 3 performance was probably due to enhanced performance in the longest uphill section, where skiers reported more use of the G3 technique with longer poles. Since it is assumed that performance in G3 and double poling has clear similarities in the contribution of the upper body to forward propulsion [15], it is reasonable to assume that the improved uphill performance with longer poles in skating on snow found here would be explained by the same mechanisms as previously found in double poling on a treadmill [5,13,17,30]. Here, longer poles resulted in lower O 2 cost, which was associated with reduced vertical displacement of CoM and longer poling time.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…While the superior improvement in the initial 200 m may be explained by faster acceleration, as previously shown for double poling in the studies by Hansen, Losnegard [8] and Losnegard et al [14], better section 3 performance was probably due to enhanced performance in the longest uphill section, where skiers reported more use of the G3 technique with longer poles. Since it is assumed that performance in G3 and double poling has clear similarities in the contribution of the upper body to forward propulsion [15], it is reasonable to assume that the improved uphill performance with longer poles in skating on snow found here would be explained by the same mechanisms as previously found in double poling on a treadmill [5,13,17,30]. Here, longer poles resulted in lower O 2 cost, which was associated with reduced vertical displacement of CoM and longer poling time.…”
Section: Discussionsupporting
confidence: 68%
“…Previously, the use of longer poles has been shown to increase skiing efficiency and performance in double poling [5,13,14,17] and in the G3 skating technique on roller skis [29]. Moreover, two previous studies showed positive effects of increased pole length on snow in the classical style [8,30]. Although there are indications from the abovementioned study on G3 roller ski skating [29] that increased pole length could be beneficial in skating, at least in some of the sub-techniques, this has not yet been examined while ski skating on snow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…the gap in monitoring methods; the gap in the psychological ability of the game; and the gap in the professional knowledge reserve of the coaches, all of which hinder the development of China's cross-country skiing project, so China's cross-country skiing project must work hard in these aspects to make a breakthrough. Practical problems [12] were solved. Recently, many sites have paid increasing attention to the application of 3D motion tracking and motion detection equipment [13].…”
Section: Calculation Of Ski Training Posture Methodsmentioning
confidence: 99%